Oxychalcogenide Perovskite Solar Cells: A Multiscale Design Approach. Issue 4 (13th September 2019) - Park, Heesoo; Baloch, Ahmer A. B.; Bentria, El Tayeb; Rashkeev, Sergey N.; Alharbi, Fahhad H.; El-Mellouhi, Fedwa
Abstract : Herein, a multiscale approach is used to design solar cells with oxychalcogenide perovskite absorbers by combining atomistic calculations and macroscale device simulations and optimization. The method involves the computation of charge carrier recombination time as well as the carriers' scattering time where lattice dynamics and multiple carrier scattering mechanisms are taken into account. Based on microscopically calculated parameters for the oxychalcogenide perovskites, a multiproperty optimization is performed to maximize the power conversion efficiency of the full device. This approach allows identifying optimal designs of some potential oxychalcogenide perovskite solar cells comprehensively. Herein, the methodology opens opportunities to accelerate lab realization and fabrication of solar cells with oxychalcogenide perovskite absorbers. Furthermore, the presented approach combines several general methods, and it should be highly beneficial in saving time and cost of device fabrication and optimization. Abstract : A multiscale approach presents the optoelectronic properties of oxychalcogenide perovskite solar cells by combining multiple‐scale methods. This approach suggests the expected maximum efficiency is 28.8% in NaNbO2 Se perovskite solar cells. Based on the materials available in databases, it is proposed that the optimal solar cell consists of aluminum‐doped zinc oxide, TiO2, NaNbO2 Se, p‐CuI, and C layers in order.